Optimum Diet for Survival and Development Growth of Laboratory-scale Culturing Harpacticoid Species, Stenhelia stephensoni (Greenwood and Tucker 1984) - Fatimah A'tirah, M.; Shabdin, Mohd Long; Khairul Adha, A.Rahim; Zakirah, Mohamad T.; Awangku Shahrir, Naqiuddin (Academic Journals Inc., 2016)
This study aims to introduce diets that are more affordable and applicable, compared to algal diet, which is time consuming and costly in maintenance. Methodology: The present study was designed for 15 days to observe the effects of different diets on population growth of marine tropical harpacticoid copepod, Stenhelia stephensoni under laboratory condition. The constant value of salinity was at 28 PSU and temperature at 27°C. Results: The diets tested were processed into juice form and are composed of single type diets and combination diets. Single type diets were made of carrot, banana, sago, catappa leaf, goat dung and seaweed, while combination diets were made with the mixture of goat dung and seaweed and goat dung with catappa leaf. Harpacticoid copepod which were fed with combination diet of goat dung and catappa leaf recorded significantly (p<0.05) higher population growth and survival (90%) compared to the rest of the treatments tested. Conclusion: The present study suggested that Stenhelia stephensoni could be a potential copepod for being commercially cultivated by as it is highly demand as food item for marine fish larvae in aquaculture industry.